ISLAMIC PRINCIPLES AS A DESIGN FRAMEWORK FOR URBAN SYSTEM: ENVIRONMENTAL CONCERN AND SUSTAINABLE DEVELOPMENT - Mohammad Arif Kamal; Tahsinur Rahman Warsi; Osama Nasir (Journal of Islamic Architecture, 2023)
It is hard to discuss Islam without bringing up the person of the Prophet Muhammad (PBUH). The urban crisis has become a significant issue due to society's Westernization. The experts say that the Islamic approach appears to be the most promising due to the urgent need for harmonization. Several concepts unmistakably found in this tradition's fundamental sources, the Hadith, the Qur'an, and the Sunnah, show how often attention the Islamic tradition has paid to both natural and urban growth. Traditional Islamic towns offered a range of experiences, from the intimate world of Home to the aspirations of the local population on a more global scale. This study critically assesses Islamic ethics and principles for sustainable urban development. According to Shari'a, the ancient Islamic law, this necessitates that the built environment be envisioned and governed in a way that advances morals and the growth of society. Urban zoning and land use rules should prioritize social integration and protect people's rights and needs since urban planning decisions affect social life in the built environment. A variety of basic Islamic ideals, such as human welfare and glory, justice and equality, central consideration, unanimity and kindness, economic development, security and safety, and environmental protection, must be considered when planning an Islamic metropolis. These principles could be a foundation for sustainable urban development wherever and whenever. In this research, traditional judgments support several pertinent Islamic beliefs. Eminent judges and jurists rendered these decisions in the early Muslims' customary courtroom settings. The primary sources of Shari'a, from which most were descended, are the Qur'an, Hadith, and Sunnah. This research also attempts to look into how Islamic design paradigms may be used to create urban settings that are more habitable, environmentally friendly, and culturally sensitive.